If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(1) + 2y = 10 Multiply 3 * 1 3 + 2y = 10 Solving 3 + 2y = 10 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2y = 10 + -3 Combine like terms: 3 + -3 = 0 0 + 2y = 10 + -3 2y = 10 + -3 Combine like terms: 10 + -3 = 7 2y = 7 Divide each side by '2'. y = 3.5 Simplifying y = 3.5
| 2(6x+4)=3x+10 | | f(-6)=2x+8 | | 10-6a=-4a+-12 | | 3(-1)+2y=10 | | 4y-6=7y-48 | | 3(-2)+2y= | | 4(3x-1)7-x=-2x+3+9x | | 2(2x+4)=5x+4 | | (8x-3y)+(-8x+3y)=16-16 | | 3z+30=51 | | (10m-30)=28 | | X-10=3(X-10) | | y=-0.08x+4.48 | | 5(3r-5)=9r+17 | | 3(2x-5)(2x-5)-(3x-7)(5-2x)=0 | | 2(3x+4)=2x+3 | | 2x+4y=156 | | 4x+-56=12 | | 3(2)-5y=10 | | 24=k(5) | | 3(13-4x)=7-16x | | 3(2)-5=10 | | 3(1)-5y=10 | | 3(0)-5y=10 | | 10x-345=12 | | 3(-1)-5y=10 | | 6x+13y=-15 | | 7x-35=6x | | 47x-241=3 | | 3(-2)-5y=10 | | 35x-250=10 | | -3x+-22=8 |